Fatigue Life Estimation Model of Repaired Components with the Expanded Stop-Hole Technique (2024)
Fatigue crack growth tests are conducted to assess the efficacy of the stop-hole crack repair method. This straightforward and widely adopted technique involves drilling a hole at the crack tip and subsequently enlarging it using a pin inserted into the hole. A fracture mechanics-based model is proposed to estimate the extension of fatigue life achieved through the implementation of the stop-hole technique. The model’s predictions are validated using data obtained from fatigue crack growth tests conducted on both unrepaired and repaired M(T) specimens, following the guidelines outlined in the ASTM E647 standard. The error of the fracture mechanics-based model was 1.4% in comparison with the fatigue tests.